Effective science communication a practical guide to surviving as a scientist - Illingworth, Sam; Allen, Grant ([IOP release 3], 2016)
Effective Science Communication: A practical guide to surviving as a scientist is devoted to the variety of ways that scientists are expected to communicate in their day-to-day professional lives. It includes practical advice on how to publish your work in scientific journals, apply for grants, and effectively communicate your research to both scientific and non-scientific audiences. There are chapters devoted to constructing a digital footprint, dealing with the media, and influencing science policy. Guiding you throughout are a number of useful exercises that will help you to become a more effective communicator, providing a helping hand in your scientific journey to not only survive, but to prosper in the process